2‐Sulfonylpyrimidines Target the Kinesin HSET via Cysteine Alkylation. Issue 31 (17th June 2019) - Förster, Tim; Shang, Erchang; Shimizu, Kenshiro; Sanada, Emiko; Schölermann, Beate; Huebecker, Mylene; Hahne, Gernot; López‐Alberca, Maria Pascual; Janning, Petra; Watanabe, Nobumoto; Sievers, Sonja; Giordanetto, Fabrizio; et al.
Abstract : Supernumerary centrosomes are a source of aneuploidy, and cells have adopted different mechanisms to avoid multipolar mitoses. The kinesin HSET is required for pseudo‐bipolar mitoses in cancer cells with amplified centrosomes and suppression of HSET activity is regarded a potential anti‐cancer approach. We report the identification of 2‐sulfonylpyrimidine inhibitors of HSET enzymatic activity. HSET inhibition results in establishment of multipolar mitoses and simultaneous inhibition of the kinesin Eg5 restored bipolar spindle formation. Correlation of structure to activity revealed that the 2‐sulfonylpyrimidinyl group is required for the activity of the compound class and that 2‐sulfonylpyrimidines covalently modify HSET. In addition, these electrophiles react with glutathione, thereby causing oxidative stress. This general reactivity needs to be taken into account if 2‐sulfonylpyrimidines will be employed in the development of biologically active small molecules. Abstract : 2‐Sulfonylpyrimidines were identified to inhibit the enzymatic activity of the kinesin HSET by covalently targeting cysteine residues and to induce multipolar mitoses and oxidative stress, thus emphasizing the pleiotropic effects of these alkylating agents in cells.